Contexual correlates of development of anganwadi children 3-6 years of rural Uttar Pradesh, India- a complex interplay - Rehman, Hossain Mehedi; Agarwal, Monika; Mahour, Pooja; Singh, Vijay Kumar; Patel, Sheetal Prasad; Yadhav, Kriti (International Journal Of Community Medicine And Public Health, 2022)
Background: The cross-sectional study was conducted in rural area of Lucknow, UP to assess the developmental status and its determinants among children aged 3 to 6 years registered in AWCs. Methods: A visit was made to the households of all the registered children (3-6 years) and parents were interviewed to obtain the sample size of 314. Results: Type of family, presence of congenital anomaly, educational status of the care giver, duration of EBF, presence of books and space to play were found to be independent predictors of the development status. Conclusions: To conclude, there is a dire need for acknowledgement and prompt redressal of this loss of developmental potential in children at an early age.